2013
DOI: 10.1245/s10434-013-3157-5
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and Temporal Trends in the Management of Occult Primary Breast Cancer: A Systematic Review and Meta-Analysis

Abstract: Background Management of occult primary breast cancer (OPBC), including the role of magnetic resonance imaging (MRI), is controversial. We conducted a pooled analysis of OPBC patients and a meta-analysis of MRI accuracy in OPBC in order to elucidate current practices. Methods A literature search yielded 201 studies. Patient-level data for clinically/mammographically OPBC from studies published after 1993 and from our institution were pooled; logistic regression examined associations between patient/study dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…Our study confirms the common use of bevacizumab for second-line systemic therapy, suggesting a pattern of second-line treatment for GB in routine care consistent with the indicated use for bevacizumab. Treatment patterns, patient populations, and outcomes may differ depending on the site of care [ 27 , 28 ]. Thus, it is noteworthy that approximately half of the physicians who prescribed bevacizumab during second-line treatment were affiliated with facilities that included teaching hospitals, whereas a lower percentage of physicians who prescribed bevacizumab were affiliated with NCI-designated comprehensive cancer centers.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirms the common use of bevacizumab for second-line systemic therapy, suggesting a pattern of second-line treatment for GB in routine care consistent with the indicated use for bevacizumab. Treatment patterns, patient populations, and outcomes may differ depending on the site of care [ 27 , 28 ]. Thus, it is noteworthy that approximately half of the physicians who prescribed bevacizumab during second-line treatment were affiliated with facilities that included teaching hospitals, whereas a lower percentage of physicians who prescribed bevacizumab were affiliated with NCI-designated comprehensive cancer centers.…”
Section: Discussionmentioning
confidence: 99%
“…Although systemic chemotherapy and endocrine therapy are believed to be performed according to the recommendations for their relatively comparative stage, locoregional managements for OBC such as breast conserving surgery (BCS), mastectomy, ALND, or its combinations have been variously implemented [ 8 , 9 ]. Previous studies suggested that BCS or ALND plus RT resulted in similar recurrence and survival rates compared to mastectomy plus ALND [ 5 - 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sixth, considerable geographical differences do exist with regard to various aspects of high‐risk PCa management. A similar scenario has been described among urologists of North America , as well as for the management of other malignancies, such as breast cancer . Possible reasons are disparities in national health systems, the availability of diagnostic and therapeutic technologies and cultural background.…”
Section: Discussionmentioning
confidence: 64%